The Position of the Indonesian Competition Commission as a State Auxiliary Organ in the Indonesian Constitutional System - M. Afif Hasbullah (IHSA Institute, 2021)
This study aimed to determine the position of the business competition supervisory commission as a state auxiliary organ in the Indonesian constitutional system. Legal writing is included in normative legal research using primary legal materials and secondary legal materials. The techniques for collecting legal materials in this study are primary and secondary legal sources. Meanwhile, the technique of collecting legal sources in this study uses the method of studying legal literature and constitutional law. Legal sources collected from the research results are then processed and analyzed using qualitative processing techniques The Indonesian Competition Commission is accountable to the President for the performance of its tasks. On the basis of the data analysis, it can be determined that the Indonesian Competition Commission is an independent institution free of the Government's influence and power. The Indonesian Competition Commission is accountable to the President for the performance of its tasks. As one of the institutions responsible for implementing Law Number 5 of 1999, this commission is responsible for the early stages of implementing the Act. Decisions taken by the Oversight Commission can be appealed to a higher court level. This commission has broad jurisdiction and has four main tasks, namely: 1) legal function; 2) administrative function; 3) mediating function, and 4) police function.